Biodiversité de l’entomofaune Carabidae (Insecta, Coleoptera) des bords de Loire : étude du site de l’île de Brain (Decize, 58) - Denux, Olivier (HAL CCSD, 2005)
Biodiversity of the Carabidae entomofauna (Insecta, Coleoptera) of the Loire riversides : study of Brain island site. The Loire riversides are known to be favourable to the fauna and the flora. The diversity of the habitats located along this river allows the reception of a riche and variable, indeed even specific, entomofauna. Nevertheless little is known on the associate insects. The site of the Brain island, in the department of Nièvre, constitutes a good example of this entomological wealth and particularly for the Carabidae, preponderant group of the soil fauna. This article puts forward this fauna and the interest of the site for this group. Les bords de Loire sont connus pour la qualité d’accueil qu’ils offrent pour la faune et la flore. Mais souvent l’entomofaune associée est peu connue voir ignorée. Or la diversité des milieux présents le long de ce fleuve permet l’accueil d’une entomofaune riche et variée, voire spécifique. Le site de l’île de Brain, dans la Nièvre, constitue un bon exemple de cette richesse entomologique et notamment pour les Carabidae, groupe prépondérant de la faune du sol. Cet article met en avant cette faune et l’intérêt du site pour ce groupe.